Phenotypic variability associated with the occurrence of imposex in Odontocymbiola magellanica from Golfo Nuevo, Patagonia - Bigatti, Gregorio (2007)
The increasing occurrence of imposex in marine gastropods has been related to their exposure to the tri-substituted organotin compounds tributyltin (TBT) and triphenyltin (TPhT), which have been widely used as antifouling agents, and has been documented for more than 200 gastropod species. Odontocymbiola magellanica, a large benthic neogastropod, showed 85^100% imposex near harbours with high marine tra⁄c in Patagonia.We evaluated if, as predicted by energy allocation hypothesis, females with imposex (FWI) were in average larger and/or heavier than normal individuals, and if there were di¡erences in shell morphometry associated with imposex, using both univariate and multivariate approaches. We detected di¡erences in two morphometric variables, but no overall e¡ect in shell shape, and *10% of reduction in body weight in FWI. In addition, the multivariate index of size suggested a positive e¡ect on FWI, in contrast with univariate analyses showing no di¡erences in shell length. The present results demonstrate that responses to TBT vary among gastropod species and that energy allocation hypothesis may be useful only under certain conditions.Odontocymbiola magellanica, a large benthic neogastropod, showed 85^100% imposex near harbours with high marine tra⁄c in Patagonia.We evaluated if, as predicted by energy allocation hypothesis, females with imposex (FWI) were in average larger and/or heavier than normal individuals, and if there were di¡erences in shell morphometry associated with imposex, using both univariate and multivariate approaches. We detected di¡erences in two morphometric variables, but no overall e¡ect in shell shape, and *10% of reduction in body weight in FWI. In addition, the multivariate index of size suggested a positive e¡ect on FWI, in contrast with univariate analyses showing no di¡erences in shell length. The present results demonstrate that responses to TBT vary among gastropod species and that energy allocation hypothesis may be useful only under certain conditions., a large benthic neogastropod, showed 85^100% imposex near harbours with high marine tra⁄c in Patagonia.We evaluated if, as predicted by energy allocation hypothesis, females with imposex (FWI) were in average larger and/or heavier than normal individuals, and if there were di¡erences in shell morphometry associated with imposex, using both univariate and multivariate approaches. We detected di¡erences in two morphometric variables, but no overall e¡ect in shell shape, and *10% of reduction in body weight in FWI. In addition, the multivariate index of size suggested a positive e¡ect on FWI, in contrast with univariate analyses showing no di¡erences in shell length. The present results demonstrate that responses to TBT vary among gastropod species and that energy allocation hypothesis may be useful only under certain conditions.*10% of reduction in body weight in FWI. In addition, the multivariate index of size suggested a positive e¡ect on FWI, in contrast with univariate analyses showing no di¡erences in shell length. The present results demonstrate that responses to TBT vary among gastropod species and that energy allocation hypothesis may be useful only under certain conditions.